Research on Liver Damage Caused by the Treatment of Rheumatoid Arthritis with Novel Biological Agents or Targeted Agents - Zhao X; Zhang C; An Y; Zhang Z; Zhao J; Zhang X; Yang Y; Cao W (Dove Medical Press, 2023)
Xin Zhao,1 Chenhao Zhang,2 Yi An,3 Zixuan Zhang,3 Jiahe Zhao,3 Xinwen Zhang,3 Yue Yang,4 Wei Cao4 1Department of Rheumatology, Guang'anmen Hospital of China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 2Department of Emergency, Wangjing Hospital of China Academy of Chinese Medical Sciences, Beijing, 100102, People's Republic of China; 3Department of School of Clinical Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 4Department of Wangjing Hospital of China Academy of Chinese Medical Sciences, Beijing, 100102, People's Republic of ChinaCorrespondence: Wei Cao, Department of Wangjing Hospital of China Academy of Chinese Medical Sciences, No. 6 Zhonghuan South Road, Chaoyang District, Beijing, 100102, People's Republic of China, Tel +86 10-84739099, Email caoweicw0@126.comAbstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by polyarticular, symmetric, and aggressive inflammation of the small joints in the hands and feet, resulting in dysfunction. With progress and development in medicine, treatment of RA is constantly evolving, making several drugs available for the treatment of RA. From the nonsteroidal anti-inflammatory drugs (NSAIDs) at the start of illness to glucocorticoids and then to conventional synthetic DMARDs (csDMARDs), biologic DMARDs (bDMARDs), and targeted synthetic DMARDs (tsDMARDs), therapeutic-use drugs for RA have been keeping pace with scientific research. However, various types of drugs have additional side effects when used over the long-term. New and emerging biological and targeted agents have been widely applied in recent years; however, the side effects have not been thoroughly investigated. In this paper, we review the research progress on liver damage caused by novel biological and targeted agents available for RA treatment. The aim is to provide a reference for rational clinical administration of such drugs.Keywords: liver damage, novel biological agents, research progress, rheumatoid arthritis, targeted agents